Marine Metabolites Modulating CB Receptors and TRP Channels - Rigano, Daniela; Formisano, Carmen; Taglialatela-Scafati, Orazio (Planta Medica, 2016)
Transient receptor potential channels and cannabinoid receptors are deputed to the regulation of sensory, homeostatic, and inflammatory events in the human organism. Therefore, their modulation promises to have relevant applications in important therapeutic areas such as inflammation, pain, and cancer. This review summarizes the contribution of marine research in this relatively young field, highlighting the potential of the chemodiversity carried by marine natural products in the discovery of new ligands.
Keywords: cannabinoid receptors; TRP channels; marine metabolites; pain and inflammation; drug discovery